1977
DOI: 10.2307/3053179
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Response to Unsatisfactory Purchases: A Survey of Perceiving Defects, Voicing Complaints, and Obtaining Redress

Abstract: A survey of consumer reactions to common purchases was conducted in 1975. Consumers perceive problems with many products and services, and voice complaints concerning about one-third of those problems. Third-party complaint processors play a very small role in buyer-seller disputes. Household status and type of problem influence perception of problems and choice of action or inaction. Satisfactory resolutions occur in somewhat more than half of voiced complaint cases. To increase voicing and fair handling of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
133
0
6

Year Published

1995
1995
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(148 citation statements)
references
References 5 publications
9
133
0
6
Order By: Relevance
“…These pathway, or pyramid, models anticipate that not all dissatisfaction evolves into a complaint but a clear conceptual link is made between them. Voiced grievances are seen as the tip of an iceberg which represents only a small proportion of dissatisfaction felt (Lempert 1980-1, Best andAndreasen 1977). On their journey up the pyramid the parties weigh up the issues at stake and the cost of various dispute pathway 'choices'.…”
Section: Introductionmentioning
confidence: 99%
“…These pathway, or pyramid, models anticipate that not all dissatisfaction evolves into a complaint but a clear conceptual link is made between them. Voiced grievances are seen as the tip of an iceberg which represents only a small proportion of dissatisfaction felt (Lempert 1980-1, Best andAndreasen 1977). On their journey up the pyramid the parties weigh up the issues at stake and the cost of various dispute pathway 'choices'.…”
Section: Introductionmentioning
confidence: 99%
“…The current study being empirical would, therefore, fill that gap. Additionally, the complexities of goods and services and the way they are marketed today pose more challenges to the consumer (Chatterjee & Sahoo, 2011;Hannigan, 1976;Merwe et al, 2014;Yuthayotin, 2015;Best & Andreasen, 1977). Ignorant consumers not being experts find it difficult to ascertain the quality, standard, as well as the performance of these products.…”
Section: Consumer Awarenessmentioning
confidence: 99%
“…The problem of consumers not knowing their rights, or the existing consumer protection laws has been studied. From the literature reviewed the problem is not peculiar to developing countries but also the developed jurisdictions (Jones & Boyer, 1971;Best & Andreasen, 1977;Schmitz, 2013). Studies reveal that consumers even in developed jurisdictions such as the UK don't know their consumer rights, consumer responsibilities as well as the existing consumer protection laws (Schuh & Kitson, 2003;Best & Andreasen, 1977;Kitson et al, 2003;Schmitz, 2013).…”
Section: Consumer Informationmentioning
confidence: 99%
“…In other words, studies across jurisdictions found the culture of under-reporting of consumer wrongs and consumer reluctance in pursuing their rights (Vidmar, 1988;Samuels & Vidman, 1986). Even in developed jurisdictions evidence abound that only an insignificant proportion of consumer grievance reaches the court or are ventilated before other redress mechanisms (Gibson, 1992;Schmitz, 2013;Fitzpatrick, 1992;L'Heureux, 1992;Best & Andreasen, 1977). This reluctance and culture of under-reporting of consumer wrongs have not been empirically explored in the context of Nigeria.…”
Section: Introductionmentioning
confidence: 99%